Dual action of pyrimidine derivatives: Targeting tamoxifen resistance in breast cancer - Jie Yuan; Geng Wang; Narasimha M. Beeraka; Hua Zhang; Qun Wang; Danfeng Zhang; Minghua Wang; Akshay Ravish; Arunachalam Chinnathambi; Sulaiman Ali Alharbi; Kanchugarakoppal S. Rangappa; Vladimir N. Nikolenko; et al. (Translational Oncology)
Introduction: Approximately 70 % of patients with breast cancer (BC) have estrogen receptor (ER)-positive tumors. Endocrine therapy is the principal treatment for these patients. Tamoxifen (TAM), a selective ER modulator, is commonly administered to premenopausal patients with ER-positive BC. However, resistance to TAM poses a major clinical hurdle as TAM-resistant BC cells often show increased proliferation and motility as well as undergo epithelial-mesenchymal transition (EMT). Objective: Pyrimidine-based small molecules were reported as both nuclear factor kappa B (NF-κB) and Wnt/β-Catenin pathway regulators. This report discovered oxazine (TRX-01) linked pyrimidine as an inhibitor of NF-kB and triazole (TTP-5) linked pyrimidine as an inhibitor of Wnt/β-Catenin signaling in TAM-resistant MCF-7 breast cancer cells (MCF-7R). Methods: Colony formation, wound healing, and Transwell assays were conducted to assess cell migration and invasion. MTT assay was used to evaluate cytotoxic effects. Western blotting was used to determine the signaling mechanisms for NF-κB and EMT phenotypes. Xenograft models were utilized to examine the in vivo effectiveness of TRX-01. Results: TRX-01 reversed TAM resistance in MCF-7R cells, whereas TTP-5 reduced the motility of MCF-7R cells. Additionally, TRX-01 inhibited the activation of the NF-κB signaling pathway in MCF-7R cells, whereas TTP-5 inhibited the EMT-like phenotype of MCF-7R cells by impairing the activation of Wnt/β-catenin signaling. The differences in the functions of the two pyrimidine structures are attributed to their additional structures bearing both TRX-01 and TTP-05. Conclusion: Pyrimidine-based TRX-01 and TTP-5 lead structures are promising agents for inhibiting the progression of TAM-resistant breast cancer cells. These results support the need for additional comprehensive in vivo and clinical studies to confirm the efficacy and safety of these compounds.